Dual purpose: Predatory hoverflies pollinate strawberry crops and protect them against the strawberry aphid, Chaetospihon fragaefolii. Issue 7 (5th May 2022) - Van Oystaeyen, Annette; Tuyttens, Ella; Boonen, Sten; De Smedt, Lien; Bellinkx, Stijn; Wäckers, Felix; Pekas, Apostolos
Abstract: BACKGROUND: Predatory syrphids are an important functional group due to their potential for providing multiple ecosystem services. Adults feed on nectar and pollen, and can be effective pollinators, while larvae are voracious predators that can reduce aphid pressure. Still, little research has addressed their potential dual function in agroecosystems. In this study, we assessed the potential of two predatory hoverflies, Eupeodes corollae and Sphaerophoria rueppellii, for delivering concurrent pollination and biological control of Chaetospihon fragaefolii in greenhouse strawberries. RESULTS: Both hoverfly species effectively pollinated strawberry flowers of two different varieties ('Elsanta' and 'Sonsation'), resulting in an increase in high‐quality marketable fruits, a reduction of fruit deformities, and higher number of seeds per fruit compared to pollinator‐excluded fruits. S. ruepellii had a significantly longer flower handling time than E. corollae, which translated to a more efficient pollination expressed as higher seed numbers per fruit after a single flower visit. By contrast, flowers that were open to multiple visits were more effectively pollinated by E. corollae, suggesting that E. corollae is potentially a better cross‐pollinator than S. rueppellii . In addition, both hoverfly species suppressed aphid populations in strawberry (var. 'Sonata'), with S. rueppellii and E. corollae reducing aphid populations by 49% and 62%, respectively. CONCLUSION: Predatory syrphids can concurrently contribute to pollination and biological control in strawberry in a greenhouse setting. © 2022 Society of Chemical Industry. Abstract : The predatory hoverflies Eupeodes corollae and Sphaerophoria rueppellii reduced strawberry aphid populations and effectively pollinated strawberry, increasing the proportion of marketable high‐quality fruits and reducing misshapen fruits.